A Triad of Highly Reduced, Linear Iron Nitrosyl Complexes: FeNO8–10. (25th August 2016) - Chalkley, Matthew J.; Peters, Jonas C.
Abstract: Given the importance of Fe–NO complexes in both human biology and the global nitrogen cycle, there has been interest in understanding their diverse electronic structures. Herein a redox series of isolable iron nitrosyl complexes stabilized by a tris(phosphine)borane (TPB) ligand is described. These structurally characterized iron nitrosyl complexes reside in the following highly reduced Enemark–Feltham numbers: FeNO 8, FeNO 9, and FeNO 10 . These FeNO 8–10 compounds are each low‐spin, and feature linear yet strongly activated nitric oxide ligands. Use of Mössbauer, EPR, NMR, UV/Vis, and IR spectroscopy, in conjunction with DFT calculations, provides insight into the electronic structures of this uncommon redox series of iron nitrosyl complexes. In particular, the data collectively suggest that TPBFeNO 8–10 are all remarkably covalent. This covalency is likely responsible for the stability of this system across three highly reduced redox states that correlate with unusually high Enemark–Feltham numbers.